Semantic Strategies in the Indonesian Translation of The Tales of Beedle the Bard - Adani Nur Sabrina (Jurnal Ilmiah Multidisiplin, 2023)
This translation analysis research aims to find semantic strategies contained in the Indonesian translation of The Tales of Beedle the Bard book and how the translators implemented them. The semantic strategies used are the theories suggested by Andrew Chesterman. Those semantic strategies include nine categories, namely synonymy, antonymy, hyponymy, converses, abstraction change, distribution change, emphasis change, paraphrase, and trope changes. The method used in this research is descriptive qualitative. The data are collected with purposive sampling and then analyzed with stratified sampling. The result shows that there are sixty-eight data found that cover all of the nine semantic strategies: two synonymies, six antonymies, ten hyponymies, two converses, two abstraction changes, fifteen distribution changes, seven emphasis changes, twenty-two paraphrases, and two trope changes. In this research, the researcher aspires to be able to broaden her own insights—as well as the readers’—about semantic strategies in translation. Therefore, this comprehension of translation strategies and theories can be helpful for upcoming translation research and projects.